Potential of Moringa oleifera saponins as a preventive of water pollution from the linear compound alkylbenzene sulfonate (LAS) - Devi Mariya Sulfa; Ikramina Yusti Amina; Hendra Susanto (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
Increasing detergent consumption in society has an impact on increasing the volume of waste, which has the potential to pollute water ecosystems. TOP Brand Data Search for 2021 states that people worldwide are more interested in using detergents to combat stubborn stains. Indonesian industrial companies are increasingly producing chemical-based detergents. The research aimed to describe the potential of Moringa oleifera saponin as an effort to prevent water pollution from the Linear Alkylbenzene Sulfonate (LAS) compound. The research method uses a rotary evaporator with organoleptic tests. The results found in M. oleifera saponin have a distinctive odour from isothiocyanate compounds, yellowish green colour, pH within 25○C (concentrate 6), the active ingredient of saponin (protease enzyme) of M. oleifera leaves was 8.5%, and specific gravity (2.5%) with a concentrate of 1.2. This research shows that the liquid Detergent produced meets Standar Nasional Indonesia (SNI), and the detergent quality was good. The saponin content of M. oleifera was an alternative for industrial companies and a preventive measure for better water ecosystem processing.